2014
DOI: 10.1007/s00436-014-4106-3
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of Urophycis brasiliensis (Gadiformes: Phycidae) as indicators of marine ecoregions in coastal areas of the South American Atlantic

Abstract: The potential value of parasites as ecosystem markers was tested by analyzing the metazoan assemblages of Urophycis brasiliensis caught in four locations distributed in three ecoregions of the Warm Temperate Southwestern Atlantic. A total of 5,001 metazoan parasites belonging to 33 species were found. The identified parasites varied across locations in terms of presence, prevalence, and abundance, and their multivariate analyses resulted in clear similarity patterns. No differences were observed between two lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…in the same hosts, except for U. brasiliensis possibly due to the smaller size of Brazilian specimens. These recurrent patterns of suitable parasite tags across host species in the southwestern Atlantic reinforce previous studies in this region showing that parasite assemblages can be used as ecosystem indicators to characterize hosts living if different zoogeographical provinces (Cantatore and Timi, 2015) and, as suggested by Pereira et al (2014) for studies at larger spatial scales, as indicators of ecoregions within zoogeographical provinces.…”
Section: Jaccardsupporting
confidence: 65%
See 2 more Smart Citations
“…in the same hosts, except for U. brasiliensis possibly due to the smaller size of Brazilian specimens. These recurrent patterns of suitable parasite tags across host species in the southwestern Atlantic reinforce previous studies in this region showing that parasite assemblages can be used as ecosystem indicators to characterize hosts living if different zoogeographical provinces (Cantatore and Timi, 2015) and, as suggested by Pereira et al (2014) for studies at larger spatial scales, as indicators of ecoregions within zoogeographical provinces.…”
Section: Jaccardsupporting
confidence: 65%
“…They also displayed latitudinal patterns of prevalence and abundance similar to those observed in previously studied host species. Indeed, parasite loads of G. carvajalregorum and C. australe were higher in Argentina than in Brazil in Cynoscion guatucupa (Timi et al, 2005), Pinguipes brasilianus (Timi et al, 2010), Trachurus lathami (Braicovich et al, 2012) and U. brasiliensis (Pereira et al, 2014), whereas the opposite pattern was observed for Hysterothylacium sp. in the same hosts, except for U. brasiliensis possibly due to the smaller size of Brazilian specimens.…”
Section: Jaccardmentioning
confidence: 48%
See 1 more Smart Citation
“…The parasite assemblages of D. auriga were, however, similar to those found on other host species in the region in terms of their composition, sharing the same set of dominant species with other sympatric fishes, namely G. carvajalregorum , C. australe and Hysterothylacium sp. These species have been identified as both typical and as indicators of this ecoregion (Pereira et al ., ). The presence of H. aduncum at high loads in the sampled fish is notable.…”
Section: Discussionmentioning
confidence: 97%
“…Lanfranchi et al [ 29 ] included data on other host species recognized as harbouring parasite assemblages representative of neighbouring zoogeographical regions, characterized by these masses of water [ 9 , 33 , 34 ]. These waters, with subtropical and sub-Antarctic origins, affected the structure of parasite communities in the ecotone by acting as sources of infective stages of helminth species (acanthocephalans, nematodes, cestodes) typical of adjacent zoogeographical units, which were considered as reliable indicators to define such transitional regions.…”
Section: Introductionmentioning
confidence: 99%